Heterometallic MOFs constructed from thiophene and furandicarboxylate ligands for heavy metal luminescence sensing. Issue 8 (3rd February 2021) - Sapianik, Aleksandr A.; Barsukova, Marina O.; Kovalenko, Konstantin A.; Samsonenko, Denis G.; Fedin, Vladimir P.
Abstract : A series of heterometallic porous MOFs were rationally designed from preorganized molecular complexes for heavy metal cation luminescence detection. Abstract : Rational design of a series of new heterometallic MOFs was carried out by the judicious choice of the corresponding synthesis conditions and ligand geometry. Three heterometallic MOFs (H2 NMe2 )[LiZn(dmf)(tdc)2 ]·DMF·H2 O (1 ), [LiZn2 Li2 Zn2 (dmf)6 (tdc)6 ]·6DMF·H2 O (2 ) and [Li2 Zn2 (dmf)2 (fdc)3 ]·2DMF·2H2 O (3 ) were obtained on the basis of the pre-synthesized pivalate complex [Li2 Zn2 (py)2 (piv)6 ]. The angle between carboxylic groups greatly affects the possibility of retaining the initial tetranuclear node in the structure of the obtained MOFs. Compound 3 demonstrates permanent porosity with a calculated BET surface area value of 287 m 2 g −1 . Compounds 2 and 3 are capable of heavy metal sorption from their nitrate solution, and a significant flare-up of the luminescence of the obtained inclusion compounds is observed, where the quantum yield of luminescence increases by an order of magnitude in the case of cadmium inclusion.